2022
DOI: 10.4103/ija.ija_332_22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single intraoperative dose of dexamethasone on glycaemic profile in postoperative patients - A double-blind randomised controlled study

Abstract: Background and Aims: The effect of a single intraoperative dose of steroids on perioperative blood sugar levels is uncertain. We hypothesised that a single dose of dexamethasone would not unfavourably alter the glucose levels of non-diabetic patients. This study aimed to evaluate the post-operative glycaemic profile after a single dose of intraoperative dexamethasone in non-diabetic patients. The presence of post-operative nausea and vomiting (PONV), pain, surgical site infection (SSI) and length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The demographic data of the 27 included articles are given in Table 1 . [ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] Overall, 13 out of 27 were judged as having a low risk of bias. [ 5 6 9 10 12 15 16 20 21 22 23 24 27 ] In contrast, 6 out of 27 had a high risk of bias,[ 4 13 14 25 28 30 ] and 8 out of 27 had some concerns regarding biases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The demographic data of the 27 included articles are given in Table 1 . [ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] Overall, 13 out of 27 were judged as having a low risk of bias. [ 5 6 9 10 12 15 16 20 21 22 23 24 27 ] In contrast, 6 out of 27 had a high risk of bias,[ 4 13 14 25 28 30 ] and 8 out of 27 had some concerns regarding biases.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] Overall, 13 out of 27 were judged as having a low risk of bias. [ 5 6 9 10 12 15 16 20 21 22 23 24 27 ] In contrast, 6 out of 27 had a high risk of bias,[ 4 13 14 25 28 30 ] and 8 out of 27 had some concerns regarding biases. [ 7 8 11 17 18 19 26 29 ] In domain 1, that is, bias arising from the randomisation process, 3 out of 27 had some concerns regarding biases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that even a single dose of dexamethasone in non-diabetic adults causes statistically significant and higher, earlier and prolonged postoperative hyperglycaemia up to 72 hours. [ 18 ]…”
Section: Contemporary Researchmentioning
confidence: 99%